TAXONOMIA Y DISTRIBUCION DE LAS ESPECIES DÉ MACRODACTYLUS LATREILLE (COLEOPTERA: MELOLONTHIDAE) EN MEXICO Y ESTADOS UNIDOS DE AMERICA - Arce Pérez, Roberto; Morón, Miguel Ángel (Instituto de Ecología, A.C., 2000)
A taxonomic review of the 27 Mexican and North American species of Macrodactylus is presénted. Six new species are described: M. batesi n. sp. from Cuautla, Jalisco; M. manantlecus n. sp. collected from the Manantlán mountain range. Jalisco; M.montanas n.sp. from the reserve of Huitepec, San Cristóbal de las Casas, Chiapas; M. pokornyanus n.sp. obtained from Atlacomulco, State of México; M. surianas n.sp. from the mountains of Atoyac, Guerrero; and M. carrilloi n.sp. from the humid mountains of Chiapas and Guatemala. Macrodactylus championi Bates is registered for the first time for Chiapas, México. A new infrageneric classification is proposed, including four groups: Group I, "lineatus") Group II, "dimidiatus") Group III murinus", Group IV "subspinosus". Host plants for nearly all the species are listed. A key to the 27 species is provided, as well as illustrations of genitalia of both sexes and types of setae coverings. The geographical and ecological distribution patterns of each species and groups of species are aiso commented.